2023
DOI: 10.17358/jma.20.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Ready-To-Eat Meal Consumer’s Intention To Use Food Delivery Apps During The Covid-19 Pandemic

Abstract: Food delivery apps (FDA) are one of the most popular types of online marketing media, providing convenience for consumers to order ready-to-eat meals. The possibility of using and ordering food through FDA has also increased with the rise of Covid-19 cases as people practice social-distancing as a form of subjective norm. This study aims to analyze factors influencing consumers' intention to use FDA during the pandemic. The primary data from online survey of 327 greater Jakarta residents who previously have or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
0
0
Order By: Relevance
“…Research results showed that the social environment, Innovativeness significantly influences online consumption intentions (Reyvina & Tunjungsari, 2022;Rizki et al 2019) and risk negatively influences online consumption intentions (Putri et al 2023). Consumption intentions also have a significant influence on online purchasing behavior (Sitohang et al 2021).…”
Section: Managerial Implicationsmentioning
confidence: 97%
“…Research results showed that the social environment, Innovativeness significantly influences online consumption intentions (Reyvina & Tunjungsari, 2022;Rizki et al 2019) and risk negatively influences online consumption intentions (Putri et al 2023). Consumption intentions also have a significant influence on online purchasing behavior (Sitohang et al 2021).…”
Section: Managerial Implicationsmentioning
confidence: 97%
“…Fernández et al, 2021;Putri et al, 2023). While there is much empirical evidence supporting the theory of reasoned action model(Choo et al, 2004;Sheppard et al, 1988; Tobias-Mamina & Maziriri, 2023), concerns have been raised about the connection between subjective norms and attitude.…”
mentioning
confidence: 99%
“…External expectations, also known as subjective norms, are thought to influence internal predispositions, such as attitude, in certain situations, such as when making new product purchases(Choo et al, 2004;Ryan, 1982). Besides, the subjective norm is a crucial determinant of attitude(Putri et al, 2023;Troise et al, 2021). Furthermore, in the realm of food delivery applications, people are more inclined to adopt food delivery applications when they see their coworkers, families, and other associated persons having a positive attitude toward using them.Choo et al (2004), Piroth et al (2020), Putri et al (2023), and Troise et al (2021) have established the significance of this correlation in the utilization of online or mobile platforms for purchasing food or groceries.Furthermore, to boost customer interest, food delivery suppliers often implement promotional pricing strategies.…”
mentioning
confidence: 99%